المصــــدر المتصيّد في العربيّة The hunting Source In Arabic Language - Saleh Kazim Ajeel صالح كاظم عجيل (Journal Of Babylon Center For Humanities Studies, 2016)
Source is the signifier name on an event of an act like hitting and honoring, an abstract of time including characters with verb in means Lafthan such as the Arabic word Alama Alman or Taqdeeran such as: Katala Ketalan, or Mu`aowethan, which deleted with an other than it, like Wa`ada Wa`dan which is a source; because the act was released and taken from it. There are two types of source: an explicit source and another perceptive interpreter source, the interpreter comes from certain structures If I want it to be past or future it is interpreted by (Enna and the verb) and if I want it to be an immediate case than it is interpreted by (Ma and the verb) and others. As our source throughout the search is the source of a perceptive interpreter but did not really include what is mentioned above, it has multiple types on context in Arab talk as a story and creation, we cannot put standard measures for it by this source as is the case of (Enna and the verb) and (Ma and the verb) and (Enna and its wrought) but it is a source that is made from context, and can read its motivations by two things: One of them: the requirements of sense, and the other grammatical industry controls. And so we can define of what it really is as much as possible, as we say: (It is the source of contextual perceptive interpreter of speech imposed by the establishment of a story or a meaning matter as conscience on what suits it or imposed by grammatical work).